ANALISIS PENDAPATAN USAHATANI JAGUNG KELOMPOK TANI RAHAYU II MOJOROTO KOTA KEDIRI - Eko Budi Santoso; Eko Wahyu Budiman; Palupi Puspitorini (grafting, 2022)
This study aims to determine the cost, yield and feasibility of corn farming by farmers. The sampling technique used was purposive sampling method, namely the Rahayu II Farmer Group who understood and knew the conditions of Corn Farming. Sources of data used are primary data and secondary data. The type of data used is quantitative data by means of observation, interviews, and documentation. The data analysis method in this study uses the BEP and R/C measurement methods. The results of the analysis of production costs are Rp. 25,430,500, revenue is Rp. 48,020,000, net profit is Rp. 22,589,500. The results of the analysis of the production BEP of 198.89kg and the price BEP of Rp. 2594.89/kg, the amount of production BEP is less than the total production value and the total price BEP is less than the product price. The results of the return cost ratio analysis are 1.88, the R/C value is more than 1. It means that this farming is feasible to do.